Jak motyl . Like a Butterfly - Pieta, Ewa (MG Production, 2004)
Verzio FF submission Przemek, a quadriplegic since birth, was unable to control the movements of his arms and legs and was also unable to speak. Until he was six he believed that he was the same as everyone else and that his mother understood the screeches which he considered to be his speech. The boy grew and matured, but everybody considered him stupid. To make matters worse, when he was eight years old, his mother – afflicted with a serious back problem – put him in a clinic. Przemek stayed there for another eight years, presumed to be a "vegetable". Gradually Przemek realized that nobody had any idea that mentally he was completely healthy. He tried to make contact by batting his eyelids, but it was no use. Finally, a miracle happened. Accidentally, a therapist discovered Przemek’s signaling and the boy’s life took a new turn. At the age of sixteen he began to learn Bliss, a system of pictorial symbols which enabled him to communicate with those around him for the first time. Although Przemek cannot speak, he now writes poems and songs and "shows how beautiful it is to live, despite or because of his handicap."